The Effects of Obesity-Related Health Messages on Explicit and Implicit Weight Bias - Rudolph, Almut; Hilbert, Anja (Frontiers in Psychology, 2017)
The pervasiveness of explicit and implicit weight bias (WB) defined as negative stereotypes and prejudice regarding one’s weight has been observed among individuals of all weight categories. As a source of WB, health messages have been discussed due to reinforcing stigmatizing notions. The present study sought to investigate whether health messages (i.e., eat healthy, become physically active) have the potential to increase explicit and implicit WB. Participants (N = 144) from the community were randomized to either an experimental group or a control group. While the experimental group was presented with health messages, the control group was presented with neutral information. Before and after manipulation, participants completed measures of explicit and implicit WB. Paired samples t tests revealed no differences in explicit WB after manipulation, however, a medium effect decrease of implicit WB in the experimental group but not in the control group was found. This study provided evidence that health messages might have differential impact to change WB. According to dual-model approaches, explicit and implicit WB tap into two different information processing systems, and thus were differentially affected by health messages. Brief exposure to health messages might have the potential to contribute to health behavior and to mitigate implicit WB.